Recreation as a scientific discipline and its historical aspects - Zaycev V.P; Iermakov S.S; Manycharyan S.V; Fedyay I.A (Kharkov National Pedagogical University, 2012)
Purpose of work - to show an importance of recreation measures for forming, renewal, strengthening and saving of students' health. The analysis of recreation measures is resulted in educational space of higher educational establishment. Concept methodology of recreation and physical recreation is expounded for the students of higher educational establishments: types of recreation and its function, recreational system, recreational districting and correlation of recreational buildings in surrounding space. The modern problems of recreation and physical recreation are reflected. It is marked that important factors in successful recreation activity it is been: level of educational preparation of workers; professionalism of doctors, doctors rehabilitation, instructors and methodists of physical culture; presence of the special territorial areas; terms for the leadthrough of employments and in a civilized manner-entertaining measures. It is marked that recreation is passive and active rest in a complex with other health measures out of production, educational, scientific and to other activity. He is directed on forming, renewal, strengthening and saving of health of a man, and also bringing him satisfaction and pleasure from these measures.